Healing properties of quina and a possible case of catalepsy considered as resurrection according to the Tradiciones peruanas by Ricardo Palma - Butrón Verástegui, Victoria Elvira (2019)
This article will analyze the traditions «Los polvos de la condesa» and «El resucitado», texts where the traditionalist Ricardo Palma relates the importance given to the properties of quina as a treatment for those suffering from fever probably caused by malaria, as well as the relationship between the so-called «resurrection» of the time and a possible state of catalepsy of unknown etiology.